Proceedings. 2001 IEEE International Symposium on Information Theory (IEEE Cat. No.01CH37252)
DOI: 10.1109/isit.2001.936176
|View full text |Cite
|
Sign up to set email alerts
|

LDPC-based space-time coded OFDM systems over correlated fading channels: performance analysis and receiver design

Abstract: We consider the performance analysis and the receiver design of low-density parity-check (LDPC) code based space-time coded (STC) orthogonal frequency-division multiplexing (OFDM) system over correlated frequency-and time-selective fading channels. I. SYSTEM DESCRIPTIONConsider an STC-OFDM system with K subcarriers, N transmitter antennas and M receiver antennas, signaling through frequency-and time-selective fading channels. Each STC code word spans P adjacent OFDM words (or slots); and each OFDM word consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(69 citation statements)
references
References 30 publications
1
68
0
Order By: Relevance
“…In this framework, the traditional approach to channel estimation, that may be used as an initial estimate in iterative or decision directed receivers [7], [8], consists of two steps. First, the least squares (LS) estimates of the channel gains over the pilot subcarriers are obtained by simply backrotating the received signal according to the knowledge of the pilot symbols.…”
Section: Introductionmentioning
confidence: 99%
“…In this framework, the traditional approach to channel estimation, that may be used as an initial estimate in iterative or decision directed receivers [7], [8], consists of two steps. First, the least squares (LS) estimates of the channel gains over the pilot subcarriers are obtained by simply backrotating the received signal according to the knowledge of the pilot symbols.…”
Section: Introductionmentioning
confidence: 99%
“…In systems like IEEE 802.11a, where the encoder does not know the channel, a single (convolutional) code is used across all subcarriers and various decoding strategies can be employed to account for the fact that some subcarriers are better than others. Another case of interest is single carrier MIMO channel, there are a host of recent papers, see for example [46], [47], [48] For full MIMO OFDM, in [53] LDPC system is compared with space-time trellis code (STTC), the LDPC-based STC can significantly improve the system performance by exploiting both the spatial diversity and the selective-fading diversity in wireless channels. Compared with the recently proposed turbocode-based STC scheme [54], LDPC-based STC exhibits lower receiver complexity and more flexible scalability.…”
Section: B Siso and Mimo Channels With And Without Ofdmmentioning
confidence: 99%
“…[11] showed that LDPC codes are effective to improve the error performance of OFDM in multipath environments. It has also been shown in [15] that LDPC based space-time coded OFDM systems are capable of efficiently exploiting the achievable spatial diversity in wireless channel. The concatenation of convolutional and LDPC channel coding is employed in OFDM system for achieving good error rate performance with reasonable complexity.…”
Section: Introductionmentioning
confidence: 99%